Hifomicetes dematiáceos en bosque mesófilo de montaña. Registros nuevos para México - Heredia Abarca, Gabriela (Instituto de Ecología, A.C., 1994)
Ten Dematiaceous Hyphomycetes of green leaves and leaf litter from two cloud forests located in the Tamaulipas and Veracruz  States are described and illustrated. Distribution and host  Information are discussed. Nine species are new records for the  Mexican mycoflora.